Performance of mycelial biomass from the mushroom Ganoderma lucidum as feed additive on growth and quality of red hybrid tilapia (Oreochromis spp.) / Grema Yerima - Grema , Yerima (2020)
The present study describes the potentiality of dietary supplement of mycelial biomass of Ganoderma lucidum (MBGL) as functional feed additives formulated along with other feed ingredients at different inclusion levels (5g/kg diet, 10g/kg diet and 15g/kg diet). A hundred and twenty (120) red hybrid tilapia were used for this experiment in duplicates treatment. Fifteen fish were allocated to each tank with an average weight of 17.0g. A six (6) week feeding trial was conducted to evaluate the effect of GL biomass on red hybrid tilapia body composition, organosomatic index, as well as hematological indices. At the end of the feeding trial, three fish were randomly selected in each tank for fillet body composition study and organosomatic indices (condition factor, hepatosomatic indices, and viscerosomatic indices). Blood samples were collected from 7 fish for hematological studies from each group of diet. The result obtained from this study shows that the dietary supplement of GL biomass has a significant (P<0.05) influence on red hybrid tilapia organosomatic indices. The inclusion of this diet as feed additives has no adverse effect on the hybrid tilapia hematological indices. Based on the findings of this study, the mycelial biomass of Ganoderma lucidum can be used as a functional feed additive to improve aquatic productivity in aquaculture. The optimum supplementation level suggested in this study is 10g/kg diet which is considered sufficient to meet the nutritional requirement of hybrid tilapia.